Development of E-LKPD Based on Scientific Literacy on Reproductive System Material to Improve High School Students Learning Outcomes and Collaboration Skills - Nurajijah, Salsa Bila; Peniati, Endah (Universitas Negeri Semarang, 2024)
Biology learning requires students to think critically, logically, factually and the reproductive system material is complicated, making it difficult for students to understand the lesson and lack collaboration skills. The aim of this research is to analyze the validity, practicality and effectiveness of scientific literacy-based E-LKPD on reproductive system material to improve high school students' learning outcomes and collaboration skills. The type of research used is Research and Development research with a pre-experimental one group pretest-posttest design. The population in the study were students of grade XI SMA Negeri 7 Semarang. The research sample selection used a purposive sampling technique with samples from class XI-5 and XI-6. The research stages include potential and problem analysis, product design, product validation, initial product revision, small-scale trials, final product revisions, large-scale trials, and final product. The research results show that the validity of the E-LKPD product based on scientific literacy on reproductive system material obtained very valid criteria with a percentage of 92,13%. The practicality of E-LKPD products based on scientific literacy on reproductive system material obtained very practical criteria with a percentage of 93,45% from teachers and 93,55% from students. E-LKPD based on scientific literacy on reproductive system material was declared effective in improving learning outcomes with an average N-gain of 0,62 and collaboration skills with a score of 90,62%. E-LKPD based on scientific literacy on reproductive system material was successfully developed in the category of very valid, very practical, and effective in improving learning outcomes and collaboration skills at SMA Negeri 7 Semarang.